The Relationship Between Work Conflict and Employee Performance in Factory Employees: Hubungan Antara Konflik Kerja dengan Kinerja Karyawan Pada Karyawan Pabrik - Kurniawan, Wella Panidia; Dewanti, Ririn (Universitas Muhammadiyah Sidoarjo, 2023)
Productivity in a company is determined by employee performance. Employee performance can be affected because there is conflict in the workplace. Conflict is a process when one person or group feels that their goals are being opposed or disagree with the other. It is known that after observing the performance of PT. X employees in Mojokerto, the results obtained in the form of problems of decreased performance which were indicated to be caused by work conflicts so that from the problems that arise the researchers intended to conduct research with the aim of knowing the relationship between work conflict and employee performance at PT. X in Mojokerto. With the number of respondents as many as 167 employees, the data analysis method used in this paper is parametric statistical analysis using Pearson product moment correlation analysis with the results of the work conflict scale reliability test which obtained Cronbach's Alpha values of 0.945 and 0.913 results of the performance scale reliability. From the results of the analysis, it can be concluded that the correlation coefficient is -0.407 with a significance value of 0.000 <0.05 which means the hypothesis is accepted, where there is a relationship between work conflict and employee performance which describes the more work conflicts, the worse employee’s performance of PT. X in Mojokerto.